Accelerated Wheat Breeding and Production in the Face of Climate Change: The Case of Morocco - Tadesse, Wuletaw; Zakaria, EL Gataa; Rachdad, Fatima Ezzahra; Lahrichi, Khaoula; Diria, Ghizlan; Amamou, Ali; Jlibene, Mohammed; Al-Shamaa, Khaled; Kehel, Zakaria (Hapres publisher, 2024)
Wheat is the most important food crop which originated in the Fertile Crescent, the cradle of human civilization. Currently, it grows an average of 220 million hectares globally with an annual production level of 810 million tons. In Morocco, wheat is grown on 3.2 million hectares, with production levels ranging from 3 to 7 million tons/year, depending on the amount and distribution of rainfall. Like many other countries in the CWANA region, wheat production in Morocco is affected by climate change, drought, heat, diseases (rusts, septoria, fusarium), and insect pests such as Hessian fly. Wheat breeding in Morocco started in the late 1920s, and since 1980, the National Institute of Agronomic Research (INRA) has released more than 52 varieties of bread wheat. This paper reviews and summarizes the wheat production and challenges, including the seed system, the wheat breeding history and methodologies, achievements, and prospects of accelerated wheat breeding, including modified shuttle breeding, doubled haploids, speed breeding, genomic selection, and hybrid wheat, which shorten breeding cycles and enhance the precision of trait selection. Rapid development and deployment of climate-smart wheat varieties, along with improved crop management technologies, are important to increase wheat production and ensure food security in the face of climate change.